Somato-Dendritic Regulation of Raphe Serotonin Neurons; A Key to Antidepressant Action - Quentin, Emily; Belmer, Arnauld; Maroteaux, Luc (Frontiers in Neuroscience, 2018)
Several lines of evidence implicate serotonin (5-hydroxytryptamine, 5-HT)in regulating personality traits and mood control. Serotonergic neurons are classically thought to be tonic regular-firing, “clock-like” neurons. Neurotransmission by serotonin is tightly regulated by the serotonin transporter (SERT) and by autoreceptors (serotonin receptors expressed by serotonin neurons) through negative feedback inhibition at the cell bodies and dendrites (5-HT1A receptors) of the dorsal raphe nuclei or at the axon terminals (5-HT1B receptors). In dorsal raphe neurons, the release of serotonin from vesicles in the soma, dendrites, and/or axonal varicosities is independent of classical synapses and can be induced by neuron depolarization, by the stimulation of L-type calcium channels, by activation of glutamatergic receptors, and/or by activation of 5-HT2 receptors. The resulting serotonin release displays a slow kinetic and a large diffusion. This process called volume transmission may ultimately affect the rate of discharge of serotonergic neurons, and their tonic activity. The therapeutic effects induced by serotonin-selective reuptake inhibitor (SSRI) antidepressants are initially triggered by blocking SERT but rely on consequences of chronic exposure, i.e., a selective desensitization of somatodendritic 5-HT1A autoreceptors. Agonist stimulation of 5-HT2B receptors mimicked behavioral and neurogenic SSRI actions, and increased extracellular serotonin in dorsal raphe. By contrast, a lack of effects of SSRIs was observed in the absence of 5-HT2B receptors (knockout-KO), even restricted to serotonergic neurons (Htr2b5-HTKO mice). The absence of 5-HT2B receptors in serotonergic neurons is associated with a higher 5-HT1A-autoreceptor reactivity and thus a lower firing activity of these neurons. In agreement, mice with overexpression of 5-HT1A autoreceptor show decreased neuronal activity and increased depression-like behavior that is resistant to SSRI treatment. We propose thus that the serotonergic tone results from the opposite control exerted by somatodendritic (Gi-coupled) 5-HT1A and (Gq-coupled) 5-HT2B receptors on dorsal raphe neurons. Therefore, 5-HT2B receptors may contribute to SSRI therapeutic effects by their positive regulation of adult raphe serotonergic neurons. Deciphering the molecular mechanism controlling extrasynaptic release of serotonin, and how autoreceptors interact in regulating the tonic activity of serotonergic neurons, is critical to fully understand the therapeutic effect of SSRIs.